Penelope crumb never forgets - "Stout, K.Shawn" (Quercus: London, 2012)
Penelope has been best friends with Patsy Cline forever. But now Patsy's got a new friend called Vera Bogg. Patsy and Vera like share secrets. And swap outfits. They even have matching best-friend necklaces. Uh oh! Penelope needs a plan to win Patsy back
Keywords: Friendship Fiction